Desenvolvimento de um veículo baseado em amido solúvel poroso para amorfização do fármaco Efavirenz - Véliz, Arturo Bismarck Linares (2020)
The solubility and dissolution of drugs that are poorly soluble in water are greatly influenced by the size of their particles, crystalline structure and physical form. Efavirenz (EFV) is a specific drug widely prescribed for HIV and belongs to class II according to the Biopharmaceutical Classification System and exhibits low solubility (aqueous solubility 9.2 μg/mL) and high permeability. Due to its low solubility, the drug has pharmacokinetic problems with a low intrinsic dissolution rate of 0.037 mg/cm 2 /min. The solubility / dissolution behavior of a drug is an essential determinant for its oral bioavailability, being the limiting step in the rate of absorption of drugs by the gastrointestinal tract. One way to increase the solubility of EFV is to seek amorphization of the drug with its incorporation into polymers, a strategy commonly used to improve the solubility of poorly soluble drugs. The objective of this research was to develop a type of porous soluble starch (PSS) as a vehicle to improve amorphization of Efavirenz (EFV). The PSS was prepared by solvent exchange method and characterized by scanning electron microscopy (SEM) in order to study its structural morphological characterization. EFV was charged by physical mixing and solvent immersion evaporation in PSS which provided a stable hydrophilic matrix with a porous structure. The solid state properties of the loaded PSS samples were characterized by SEM, Fourier transform infrared spectroscopy (FTIR), differential exploratory calorimetry (DSC) and X-ray diffraction (XRD). The FTIR spectrum of the PSS/EFV system obtained showed the characteristic peaks attributed to efavirenz at 2259 cm-1 corresponding to the vibrations of the C≡C and the highest intensity peak at 1602 cm-1 due to the carbonyl group vibration (C=O). The peaks in the region between 1263 cm-1 and 1038 cm-1 are due to the CF3 group vibration, confirming the presence of EFV in the PSS polymer matrix. SEM micrographs showed that the EFV absorbed in PSS was partially present in crystalline form distributed on the surface of PSS and in amorphous form distributed in the pores of PSS. DSC results showed the thermal behavior of efavirenz-loaded porous starch, where an endothermic peak corresponding to the porous starch gelatinization temperature is evidenced, in addition to the EFV thermal behavior identified by an endothermic peak in the temperature range of 137- 140 °C. In some formulations, the EFV endothermic peak disappeared, which can be attributed to its amorphous character. This fact was confirmed by X-ray diffraction patterns where there are no crystalline peaks of efavirenz, indicating that the drug in these proportions is well dispersed in the polymeric matrix and its recrystallization is restricted. From these results, this study demonstrates the potential significant potential for the use of PSS as a new delivery system for poorly water soluble medicines.